PENGEMBANGAN BAHAN AJAR BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) MATERI KELISTRIKAN UNTUK SEKOLAH DASAR - Yuanita Yuanita; Feni Kurnia (Universitas Muhammadiyah Surakarta, 2019)
This research aims to develop STEM (Science, Technology, Engineering, And Mathematics) based teaching material of electrical material for primary schools. This RD study used 4D design; Define, Design, Develop and Disseminate. The instruments used are documentation, expert validation sheet, interview sheet, and feasibility test. Based on the first stage of the development; curriculum analysis, materials, and teaching materials, the second stage; specification of teaching materials design, the third stage; content analysis trhough construct validation with percentage value; 97% of the first material validator, 80% of second material validator, 82% of media validator, and 92% of language validator. The test was done to the small and huge scales of the sixth grade elementary school students with each average value was 96% and 99%. As the teaching materials user, teachers’ testing response was conducted at the fourth stage with the average value of 100%. Based on the results above, it can be summed up that the STEM – based teaching materials with high feasibility can be used for learning teaching materials.